Analisis Pengaruh Variasi Faktor Daya terhadap Efisiensi dan Regulasi Tegangan Transformator Distribusi Tiga Fasa 240 kVA Menggunakan MATLAB - Agung Budi Muljono; Muhammad Rivaldi Harjian (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2026)
Power factor is one of the key parameters affecting the performance of distribution transformers, particularly in terms of efficiency and voltage regulation. This study aims to analyze the effect of power factor variations on the efficiency and voltage regulation of a 240 kVA three-phase distribution transformer using MATLAB simulation. The power factor was varied from 0.8 lagging to 0.8 leading under the assumption of constant load power, allowing quantitative observation of performance changes. The simulation results show that the maximum efficiency of 98.334% is achieved at unity power factor (cos φ = 1). When the power factor decreases to 0.8, the efficiency drops to 97.927% for both lagging and leading conditions. This efficiency reduction is caused by the increase in load current as the cos φ value decreases, which leads to higher copper losses (I²R). Although the decrease in efficiency is relatively small, its impact can become significant in long-term operation. On the other hand, voltage regulation exhibits different trends under lagging and leading conditions. At 0.8 lagging power factor, the voltage regulation reaches 3.152% and decreases to 1.163% at unity power factor. Under leading conditions, the regulation becomes negative, reaching −1.307% at 0.8 power factor, indicating a voltage rise due to the dominance of the transformer’s reactance component. Overall, operating the transformer at a power factor close to unity provides the most optimal performance in terms of efficiency and voltage stability, and it is essential in planning reactive power compensation in power distribution systems.